Flexibility in Pragmatic Nuance: The Cognitive Edge of Bilingualism in Language Comprehension and Production - Natsir, Nurasia; Aliah, Nuraziza (REiLA : Journal of Research and Innovation in Language, 2024)
This study uniquely explores the disparities in pragmatic marker comprehension and production between bilingual and monolingual groups, aiming to elucidate the cognitive advantages associated with bilingualism. Utilizing a mixed-methods approach, the research incorporated standardized linguistic assessments and observational analyses to evaluate 200 participants, equally divided between bilinguals and monolinguals, ensuring demographic balance. The results indicate that bilingual individuals significantly outperform monolinguals in both comprehension and production of pragmatic markers. Specifically, bilingual participants scored higher on average in both the comprehension test (M = 85.6, SD = 5.3) and the production test (M = 82.4, SD = 5.1), compared to monolinguals who scored an average of 74.2 (SD = 6.8) and 70.3 (SD = 6.4) respectively. Independent samples t-tests confirmed these differences were statistically significant (p < 0.001). Further, these performance advantages persisted even after adjusting for age, gender, and education level, demonstrating the robustness of the bilingual advantage. Qualitative observational analyses supported these quantitative findings, revealing that bilingual participants used pragmatic markers with greater nuance and contextual appropriateness. Thematic analysis highlighted their higher metalinguistic awareness and cognitive flexibility, enabling them to navigate complex pragmatic contexts more effectively. Factors such as language exposure, age of acquisition, socioeconomic status, motivation, and language complexity were identified as influential in these outcomes. These findings advocate for the integration of bilingual education programs to enhance cognitive and linguistic capabilities, essential for effective communication in a globalized context.